Stray dogs inside and outside of official markets of Villa El Salvador district in Lima, Peru - Chávez V., Carolina (2016)
The aim of the study was to estimate the population of stray dogs inside and outside 21 official markets of the district of Villa El Salvador, Lima, Peru. An epidemiological form was developed and the number and characteristics of dogs per market (sex, size, number of lactating females, welfare status), and their proximity to selling food stalls were registered. The total population of stray dogs was 518 and 568 inside and outside respectively (24.6 ± 4.9 y 27.1 ± 7.7 dogs per market respectively). The results showed the need to apply the relevant rules governing the presence of stray dogs in the markets to prevent potential problems that could affect public health.